A desterritorialização das crianças e dos adolescentes face à UHE Belo Monte: uma análise a partir dos RUC São Joaquim e Laranjeiras em Altamira-PA - CONCEIÇÃO, Ronicleici Santos da (Universidade Federal do Pará, 2020)
The present article intends to analyze the deterritorialization of children and teenagers relocated to São Joaquim and Laranjeiras Urban Collective Resettlements in Altamira, southwestern Pará, characterizing the dynamics and life conditions on the process of reterritorialization. To do that, the utilized method was qualitative research, documental research in the protection institutions of children and teenagers as well as in organs and institutions linked with Belo Monte project. Besides that, semistructured interviews were also realized with children, teenagers and adults, as well as drawings as a way to capture the perception of the subject on multiple spaces. The deterritorialization is the motto of the rupture of the material and immaterial relations on the use and appropriation of the territory from the subjects in analysis, triggered by the insertion of Belo Monte HPP, aside from the difficulties of adaptation to the new living space. Considering that, in mid-2015 and 2016 the São Joaquim and Laranjeiras UCRs were analyzed and it was noted lacks and deficiencies of basic education, health and leisure services who consequently has directly interfered on the conditions of children and teenagers, being possible to observe throughtout the drawings and interviews a great feeling of belonging to the original territories, specially because of the partial or total rupture of family and community sociability nets.